O processo criativo do design gráfico: embalagem - Sarközy, Marta Simões (2007)
This paper is whithin the field of visual communication, more specifically, within the graphic design of packaging. The graphic design of packaging consists in the creation of texts, informations and images printed over paper, metal, glass plastic and other laminated surfaces, in which the products are wrapped and sold. Design is a creative process guided by pre-defined concepts to attend certain strategic demands based on commercial, operational, legislative and aesthetic direction. In this exercise, pervade the simbolic and cultural associations, language, art concepts, a certain ideological bias on its project procedure, the sensible, the imagination, the technique and the science in order to compose the visual communication. The fundaments of design are based on dicotomies, such as form and function, tecnique and art, science and art, reason and intuition, objectivity and subjectivity. Observing the documents of the creative process, from the stand point of methodology of the genetic analysis from a semiotic perspective, we intend to point out that design is a mediative activity in which sensibility interacts with intelectual decisions, called by some as rational, technical or scientifical. By the registers of the creative process came from the Portuguese agencies DIVIDENDO and CONCEITO GRÁFICO, as well as the Brazilian IN DESIGN and MÜLLER CAMACHO, we ll perform a critical attendence of the connections and systems enfolded in the development of this communication which ultimate aim is to seduce and fidelize the consumer. Based on these documents, we intend to examine and compare the graphic design creative proceedings by the methodology of genetic critique. However, at the moment in which the documents show relations with culture, we need the support of Iuri Lotmans theories of culture and Edgar Morin approach concerning complexity. As we can see, the language of the visual communication of the packaging is exclusive and standardized: is a message transmitted by a fast and artificial text of culture which operates according to the consumer s logic. In this study we shall argue about the generalizations and the singularities, differences and facts in common inside the creative criterion of each graphic designer, as well as restrictions and tendencies concerning the production of the NEW. The task of a designer is to find an association between the sensible and the functional elements, in order to idividualize the language of the packaging. Based on this point of view and with the material of the angencies we intend to nvestigate in which aspect the cultural issues affect a creation of package design